Haematopoietic cell transplantation for haemophagocytic lymphohistiocytosis: experience at a single centre. (29th September 2015) - Jorgensen, M; Tatevossian, R; Dowse, R; Webb, D; Goulden, N; Amrolia, P; Veys, P; Nansuri, V; Rao, K
Abstract : Introduction: Haemophagocytic lymphohistiocytosis (HLH) is a rare disorder of immune dysregulation that may be inherited or acquired. Causative genetic mutations are seen in around 50% of cases of primary HLH. Secondary HLH may be triggered by infections (most commonly viral), or by other conditions including malignancies and rheumatological disorders. Diagnostic criteria include prolonged high fever, hepatosplenomegaly, cytopenias and characteristic biochemical markers including elevated triglycerides, ferritin and low fibrinogen. Haematopoieitic cell transplantation (HCT) is the only curative treatment for primary HLH. The authors present their experience of HCT for HLH in a single centre over a 14 year period. Materials and Methods: A retrospective case-note review was performed for all patients who fulfilled the diagnostic criteria for HLH, between 1994 and 2008. Data were collected for patients who had undergone HCT, or had died prior to HCT. Results: 67 patients fulfilled criteria for HLH. Sixteen of 67 (24%) died prior to HCT. Fifty patients proceeded to HCT, of whom 35 (70%) remain alive and in remission. The mean time from diagnosis to HCT was 7 months. The median age at diagnosis was 0.35 years (range 0.1–9.8), 32/50 were male. Twelve received haploidentical grafts, 14 matched family donor, 11 matched unrelated donor, 11 mis-matched unrelated donor and 2 mis-matched family donor grafts. Twenty-three had myeloablative, 25 reduced intensity and 2 minimal intensity conditioning. After 1999 all patients having HCT for HLH underwent reduced intensity HCT. 15/50 (30%) patients died post-HCT. Causes of death were: pneumonitis (3), veno-occlusive disease (2), infections (3), cardiac failure (1), bleeding (1), seizure (1), EBV-related lymphoproliferative disease (1), drug toxicity (1), secondary AML and disease recurrence (1). Overall 9/21 (43%) patients are surviving from the cohort diagnosed prior to 2000, and 31/46 (67%) post 2000. Conclusion: Outcome for HLH has improved with time reflecting earlier diagnosis and disease control, and the use of reduced intensity HCT with HLA matched donors. However, significant mortality from disease and from HCT related complications still remains and further progress is required.